Computer-aided design and optimization of fixtures for plastic parts machining - Vukelić, Djordje; Simunovic, Goran; Saric, Tomislav; Matin, Isidora; Savkovic, Borislav; Lazarevic, Milovan; Tadic, Branko (Journal of Production Engineering, 2023)
Reviewed and verified in this paper is a system which integrates functions of fixture design and optimization. The system was developed for machining of plastic parts. Due to specific characteristics of plastic parts, the system allows optimization of location of fixture elements for clamping and locating, using minimum deformation of plastic parts as the goal function. The paper present the basic steps of the methodology applied, reviews specific segments of the system, and illustrates its applicability on a study case featuring operations of drilling and milling of ABS parts.